Evaluation of the mechanical properties and clinical application of nickel–titanium shape memory alloy anal fistula clip - Deng, Heng; Li, Ming; Fang, Xiaoli; Zhang, Jun; Wang, Jianmin; Tang, Kun; Tang, Ran; Jia, Ru; Han, Ying; Shi, Yang; Dong, Yu'ang (Frontiers in Surgery, 2023)
Objection To investigate the mechanical properties of nickel-titanium shape memory alloy anal fistula clip (NiTi-AFC) as well as study the surgical method of treating anal fistula and evaluate its clinical efficacy.Methods Anal fistula clip was formed in nickel-titanium alloy with a titanium content of 50.0-51.8%. The mechanical properties, chemical properties were tested. 31 patients with anal fistula were enrolled between January 1, 2020, and January 1, 2023. All patients underwent internal orifice closure surgery using NiTi-AFC, and anorectal magnetic resonance or ultrasound was performed before surgery and 6 months after surgery for diagnosis and evaluation. Fistula cure rates, length of stay, perianal pain, and Wexner incontinence scores were retrospectively compared between patients treated with NiTi-AFC and patients treated with other surgical methods.Result NiTi-AFC has a density of 6.44-6.50g•cm -3 , the shape restoring force of 63.8 N.The corrosion rate of NiTi-AFC in 0.05% hydrochloric acid solution at atmospheric pressure, 20℃ is about 6.8×10 -5 g•(m•h) -1 . 31 patients (male/female :19/12, age :43.7±17.8 years) were included. Among them, 22.6%(7) had multiple anal fistula, 16.1%(5) had high anal fistula, and 48.3% (15) had perianal fistula Crohn's disease.12.9%(4/31) did not achieve primary healing, underwent fistula resection, and eventually recovered. Retrospective analysis showed that the fistula healing rate, length of stay, and anal pain of NiTi-AFC treatment were similar to those of other traditional surgeries, but the Wexner incontinence score was significantly lower.NiTi-AFC has shape memory properties, corrosion resistance, super elastic effect, and surface cell adhesion. It is applied to internal orifice closure surgery of anal fistula with good therapeutic effect and can protect the anal function.